Afro-Latinoamérica, 1800-2000 - Andrews, George Reid, 1951- (Tiempo emulado, 2007)
Covering the last two hundred years, this book examines how African-descended people made their way out of slavery and into freedom, and how, once free, they helped build social and political democracy in Latin America.